Alkali-free glass
Patent Information
- Application Number
- JP2023128721
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-04-27
- Filing Date
- 2023-08-07
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2039-04-23
AI Technical Summary
【0010】 本発明の無アルカリガラスは、高い紫外線透過率を有しながら、所望の値に調整された熱伝導率を有している。従って、バーナー炎などの加熱手段によって加熱効率よく製造することができ、薄型ディスプレイや有機EL等の各種電子装置用のガラス基板または支持ガラス基板として適した高品質の無アルカリガラスを提供することができる。
Smart Images

Figure 0007643493000001 
Figure 0007643493000002 
Figure 0007643493000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an alkali-free glass, and more particularly to an ultraviolet-transmitting alkali-free glass suitable as a glass substrate or a supporting glass substrate used in the manufacture or manufacturing process of various electronic devices. [Background technology]
[0002] In recent years, there is an increasing need for glass substrates with high ultraviolet transmittance. Examples of such substrates include glass substrates in liquid crystal flat panel displays and the like, which include a structure in which two glass substrates are bonded together using an ultraviolet-curable resin, and supporting glass substrates for manufacturing organic light-emitting diodes (OLEDs) (e.g., flexible OLEDs including a polyimide layer) that are manufactured by laminating them on a supporting glass substrate. In the latter example, after the OLED manufacturing process, the adhesive layer on the supporting glass substrate is debonded through ultraviolet irradiation, and the supporting glass substrate is peeled off from the OLED. For devices characterized by being lightweight, thin, or flexible, such supporting glass substrates are useful in order to ensure the necessary strength during the manufacturing process.
[0003] If these glass substrates contain alkali metal oxides, the alkali metal ions will diffuse into the thin film formed on the substrate, deteriorating the film properties, and therefore these glass substrates are required to be alkali-free glass that does not substantially contain alkali metal ions.
[0004] Patent Documents 1 to 3 describe alkali-free glass substrates having an ultraviolet ray transmittance of 40 to 85% or 50 to 85% at a wavelength of 300 nm when converted into a substrate having a thickness of 0.5 mm. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2014 / 175215 [Patent Document 2] Japanese Patent Application Publication No. 2006-36625 [Patent Document 3] Japanese Patent Application Publication No. 2006-36626 Summary of the Invention [Problem to be solved by the invention]
[0006] Generally, mass-produced glass contains iron due to the raw materials and manufacturing process. Iron is dissolved in glass as Fe 2+ Or Fe 3+ In particular, Fe 3+ Since iron has absorption in the wavelength range of 300 nm or less, it is considered that reducing the amount of iron in the glass is one way to increase the ultraviolet transmittance of alkali-free glass (hereinafter simply referred to as "glass"). However, reducing the amount of iron in the glass increases the amount of Fe in the melting process. 2+ The amount of infrared absorption by the glass decreases, and as a result, the thermal conductivity of the glass increases. Then, when glass is manufactured in a kiln by heating the glass base material with the heat rays of a burner flame, the temperature distribution of the molten glass base material in the kiln becomes small, so the convection speed decreases and the bubble quality and homogeneity of the final product tend to deteriorate. This is because fining (removal of bubbles) and achieving homogeneity depend on the existence of sufficient convection.
[0007] An object of the present invention is to provide an alkali-free glass that has high ultraviolet transmittance and can appropriately adjust thermal conductivity. [Means for solving the problem]
[0008] The inventors discovered that by increasing the β-OH of glass, it is possible to improve infrared absorption while maintaining a low iron content and high ultraviolet transmittance, i.e., to lower the thermal conductivity. However, if the thermal conductivity is lowered too much, the molten glass base material at the bottom of the kiln becomes too cold and becomes difficult to flow, so it is important to keep the thermal conductivity within an optimal range by adjusting the iron content and β-OH.
[0009] The present disclosure includes the following embodiments. [1] The strain point is 650°C or higher, and the average thermal expansion coefficient at 50 to 350°C is 30×10 -7 ~45×10 -7 / ℃, and the glass viscosity is 10 2 The temperature T2 at which the thermal expansion coefficient becomes dPa s is 1500°C to 1800°C, In mole percent based on oxide SiO2: 62-70%, Al2O3: 9-16%, B2O3: 0.5-12%, MgO: 5.6-10%, CaO: 4-10%, SrO: 0.1-6%, Fe2O3: 0.001-0.04% MgO+CaO+SrO+BaO is 15.6-20.5%; An alkali-free glass having a value represented by the following formula A of 7 to 30. In formula A, [Fe2O3] is the value of the mole percent of total iron converted to Fe2O3, and [β-OH] is the value expressed in units of / mm. Formula A: (3.119×10 -4 T2 2 -0.2014T2-17.38)[Fe2O3]+(6.434×10 -7 T2 2 +0.0144T2-7.842)[β-OH] [2] The alkali-free glass according to [1], having a β-OH value of 0.35 to 0.85 / mm. [3] Glass viscosity is 10 2 The alkali-free glass according to [1] or [2], having an effective thermal conductivity of 40 to 65 W / m·K at a temperature T2 where the glass has a thermal conductivity of 40 dPa·s. [4] The alkali-free glass according to any one of [1] to [3], which has a transmittance of 50% or more at a wavelength of 300 nm based on a plate thickness of 0.5 mm. [5] The alkali-free glass according to any one of [1] to [4], which is in the form of a glass plate and has a thickness of 0.05 mm to 3 mm. [6] The method for producing an alkali-free glass according to any one of [1] to [5], comprising a step of shaping molten glass by a float process or a fusion process. [7] A display panel comprising the alkali-free glass according to any one of [1] to [5]. [8] A semiconductor device comprising the alkali-free glass according to any one of [1] to [5]. [9] An information recording medium comprising the alkali-free glass according to any one of [1] to [5]. The present disclosure further includes the following embodiments.
[10] The strain point is 650°C or higher, and the average thermal expansion coefficient at 50 to 350°C is 30×10 -7 ~45×10 -7 / ℃, and the glass viscosity is 10 2 The temperature T2 at which the thermal expansion coefficient becomes dPa s is 1500°C to 1800°C, In mole percent based on oxide SiO2: 62-70%, Al2O3: 9-16%, B2O3: 0-12%, MgO: 3-10%, CaO: 4-12%, SrO: 0-6%, Fe2O3: 0.001-0.04% MgO+CaO+SrO+BaO 12~25% and β-OH value is 0.35~0.85 / mm; Alkali-free glass.
[11] The alkali-free glass according to
[10] , wherein the value represented by the following formula A is 7 to 30: In formula A, [Fe2O3] is the molar percentage of total iron converted to Fe2O3, and [β-OH] is the value expressed in units of / mm. Formula A: (3.119×10 -4 T2 2 -0.2014T2-17.38)[Fe2O3]+(6.434×10 -7 T2 2 +0.0144T2-7.842)[β-OH]
[12] Glass viscosity is 10 2 The alkali-free glass according to
[10] or
[11] , having an effective thermal conductivity of 40 to 65 W / m·K at a temperature T2 where the glass has a thermal conductivity of 40 dPa·s.
[13] The alkali-free glass according to any one of
[10] to
[12] , which has a transmittance of 50% or more at a wavelength of 300 nm based on a plate thickness of 0.5 mm.
[14] The alkali-free glass according to any one of
[10] to
[13] , which is in the form of a glass plate and has a thickness of 0.05 mm to 3 mm.
[15] The method for producing an alkali-free glass according to any one of
[10] to
[14] , comprising a step of shaping molten glass by a float process or a fusion process.
[16] A display panel comprising the alkali-free glass according to any one of
[10] to
[14] .
[17] A semiconductor device comprising the alkali-free glass according to any one of
[10] to
[14] .
[18] An information recording medium comprising the alkali-free glass according to any one of
[10] to
[14] . Effect of the Invention
[0010] The alkali-free glass of the present invention has a high ultraviolet transmittance and a thermal conductivity adjusted to a desired value, and therefore can be efficiently produced by heating using a heating means such as a burner flame, and can provide a high-quality alkali-free glass suitable as a glass substrate or a supporting glass substrate for various electronic devices such as a thin display or an organic electroluminescence (EL) display. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] In this embodiment, "alkali-free" glass means glass that does not substantially contain alkali metal oxides such as Na2O and K2O. "Substantially free" means that no components are added except for those that are inevitably contained as impurities. In the present invention, "substantially free" means that the content of alkali metal oxides is, for example, 0.5% or less, preferably 0.2% or less, more preferably 0.1% or less, more preferably 0.08% or less, even more preferably 0.05% or less, and most preferably 0.03% or less (mol % on an oxide basis).
[0012] The alkali-free glass according to the present embodiment contains a predetermined amount of metal oxide components in addition to SiO2 and Al2O3 that form the skeleton of the glass. The content of each component in the alkali-free glass according to the present embodiment on an oxide basis will be described below. In the following, "%" means "mol%" unless otherwise specified.
[0013] The SiO2 content is 62 to 70%. The SiO2 content is preferably 63% or more, more preferably 64% or more, even more preferably 65% or more, and particularly preferably 65.5% or more. If the SiO2 content is less than the lower limit, the strain point is low, the thermal expansion coefficient and specific gravity are high, and the hydrofluoric acid resistance tends to be poor. Hydrofluoric acid and buffered hydrofluoric acid (BHF: a mixture of hydrofluoric acid and ammonium fluoride) are chemicals commonly used in etching processes related to semiconductor formation and thinning. On the other hand, the SiO2 content is preferably 69% or less, more preferably 68.5% or less, even more preferably 68% or less, and particularly preferably 67.5% or less. If the SiO2 content exceeds the upper limit, the glass viscosity becomes 10 2 The solubility tends to decrease and the devitrification temperature tends to increase, e.g., the temperature (T2) at which the poise becomes high (dPa·s).
[0014] The content of Al2O3 is 9 to 16%. The content of Al2O3 is preferably 10% or more, more preferably 10.5% or more, even more preferably 10.8% or more, and particularly preferably 11% or more. If the content of Al2O3 is less than the lower limit, phase separation control becomes difficult, the strain point decreases, and the thermal expansion coefficient tends to increase. On the other hand, the content of Al2O3 is preferably 15% or less, more preferably 14% or less, even more preferably 13.8% or less, and particularly preferably 13.5% or less. If the content of Al2O3 exceeds the upper limit, T2 increases, the solubility deteriorates, and the devitrification temperature also tends to increase.
[0015] The content of B2O3 is 0 to 12%. Although B2O3 is not essential, it can be contained in order to improve the melting reactivity of glass during production, to lower the devitrification temperature, and to improve the BHF resistance. The content of B2O3 is preferably 0.5% or more, more preferably 0.8% or more, even more preferably 1% or more, and particularly preferably 1.2% or more. On the other hand, the content of B2O3 is preferably 11% or less, more preferably 10% or less, even more preferably 9% or less, and particularly preferably 8.5% or less. If the content of B2O3 exceeds the upper limit, the strain point tends to decrease.
[0016] The content of MgO is 3 to 10%. The content of MgO is preferably 4% or more, more preferably 4.5% or more, even more preferably 5% or more, and particularly preferably 5.5% or more. Compared with other alkaline earths, MgO has the effect of improving solubility, reducing specific gravity, and further improving hydrofluoric acid resistance without increasing the thermal expansion coefficient, but if the content is less than the lower limit, it is difficult to fully obtain these effects. On the other hand, the content of MgO is preferably 9.7% or less, more preferably 9.5% or less, even more preferably 9.3% or less, and particularly preferably 9.1% or less. If the content of MgO exceeds the upper limit, the devitrification temperature may become high.
[0017] The CaO content is 4 to 12%. The CaO content is preferably 4.2% or more, more preferably 4.5% or more, even more preferably 4.7% or more, and particularly preferably 5% or more. CaO is the second most alkaline earth metal after MgO in that it does not increase the thermal expansion coefficient and does not excessively lower the strain point, and it also improves the solubility like MgO. If the content is less than the lower limit, it is difficult to fully obtain these effects. On the other hand, the CaO content is preferably 11.5% or less, more preferably 11% or less, even more preferably 10.5% or less, and particularly preferably 10% or less. If the CaO content exceeds the upper limit, the thermal expansion coefficient tends to increase. Also, if the CaO content exceeds the upper limit, the devitrification temperature may increase.
[0018] The content of SrO is 0 to 6%. SrO can be contained in order to improve the melting property during glass production without increasing the devitrification temperature of the glass. The content of SrO is preferably 0.1% or more, more preferably 0.5% or more, even more preferably 1% or more, and particularly preferably 1.2% or more. On the other hand, the content of SrO is preferably 5.8% or less, more preferably 5.5% or less, even more preferably 5.3% or less, and particularly preferably 5.0% or less. If the content of SrO exceeds the upper limit, the specific gravity and thermal expansion coefficient increase, and the hydrofluoric acid resistance also tends to deteriorate.
[0019] BaO is not an essential component, but can be contained in order to improve the solubility without increasing the devitrification temperature of the glass. However, if a large amount of BaO is contained, the specific gravity increases and the average thermal expansion coefficient tends to become too large. Therefore, the content of BaO is preferably 1% or less, more preferably 0.5% or less, and even more preferably 0.1% or less. It is particularly preferable that BaO is not substantially contained.
[0020] In the alkali-free glass according to the present embodiment, the total amount of alkaline earth metal oxides, i.e., MgO+CaO+SrO+BaO (hereinafter also referred to as "RO"), is 12 to 25%. RO is preferably 13% or more, more preferably 14% or more, even more preferably 15% or more, and particularly preferably 15.5% or more. If RO is less than the lower limit, the melting property of the glass is deteriorated. Also, if RO is less than the lower limit, the devitrification temperature may increase. On the other hand, RO is preferably 23% or less, more preferably 21% or less, even more preferably 20.5% or less, and particularly preferably 20% or less. If RO exceeds the upper limit, the strain point is lowered, the specific gravity is increased, the thermal expansion coefficient is increased, and the hydrofluoric acid resistance tends to be reduced.
[0021] The iron content in the alkali-free glass according to the present embodiment is 0.001 to 0.04% calculated as Fe2O3. Fe2O3 is preferably 0.002% or more, more preferably 0.003% or more, even more preferably 0.0035% or more, and particularly preferably 0.004% or more. Fe2O3 is preferably 0.03% or less, more preferably 0.02% or less, even more preferably 0.018% or less, and particularly preferably 0.016% or less. As described above, since the content of Fe2O3 contributes to a decrease in ultraviolet transmittance, it is considered preferable to have a low content in glass that requires ultraviolet transmittance, but if the Fe2O3 content of glass is reduced, the infrared absorption ability will also decrease and the thermal conductivity will increase. In this embodiment, the above-mentioned Fe2O3 content range was found as a result of detailed consideration of the balance with β-OH, which will be described later.
[0022] In addition to the above components, the glass according to the present embodiment may contain any of ZrO2, ZnO, SO3, F, Cl, and SnO2, either alone or in combination, in a total amount of 2% or less, preferably 1% or less, and more preferably 0.5% or less, in order to improve its solubility, clarity, formability, and the like.
[0023] On the other hand, the glass according to the present embodiment preferably does not substantially contain P2O5 in order to prevent deterioration of the characteristics of a thin film of metal or oxide, etc., provided on the surface of the glass sheet.Furthermore, in order to facilitate recycling of the glass, it preferably does not substantially contain PbO, As2O3, or Sb2O3.
[0024] The alkali-free glass according to the present embodiment may have a β-OH value, which is an index of water content, of 0.35 to 0.85 / mm. The β-OH value is preferably 0.40 / mm or more, more preferably 0.45 / mm or more, even more preferably 0.48 / mm or more, and particularly preferably 0.50 / mm or more. The β-OH value is preferably 0.8 / mm or less, more preferably 0.77 / mm or less, even more preferably 0.75 / mm or less, and particularly preferably 0.7 / mm or less. Increasing the β-OH value can reduce the thermal conductivity without reducing the UV transmittance. However, reducing the thermal conductivity too much can cause the above-mentioned problems. The present inventors have found the above-mentioned β-OH value range that is particularly suitable for producing highly UV-transmitting alkali-free glass by analyzing the contribution of each of the two to the reduction in thermal conductivity near the melting temperature using combinations of different iron amounts and β-OH values.
[0025] Methods known to those skilled in the art can be used to adjust the β-OH value in alkali-free glasses, for example, by using hydroxides as glass frits (especially sources of Mg or Ca) or by increasing the water vapor partial pressure or dew point of the melting atmosphere to adjust the β-OH value higher.
[0026] The alkali-free glass according to the present embodiment has a strain point of 650°C or higher. If the strain point is lower than 650°C, thermal shrinkage may occur during heat treatment required for the manufacture of electronic devices, resulting in a decrease in yield. The strain point is preferably 655°C or higher, more preferably 660°C or higher, even more preferably 663°C or higher, and particularly preferably 665°C or higher. If the strain point is too high, the temperature of the molding device must be increased accordingly, which tends to reduce the life of the molding device, so the strain point is preferably 770°C or lower, more preferably 750°C or lower, even more preferably 740°C or lower, and particularly preferably 730°C or lower.
[0027] The alkali-free glass according to the present embodiment has an average thermal expansion coefficient of 30×10 at 50 to 350° C. -7 / ℃~45×10 -7 / ℃. The average thermal expansion coefficient from 50 to 350℃ is 33×10 -7 / ℃ or more is preferable, 35×10 -7 / ℃ or more is preferable, and 36×10 -7 / ℃ or more is more preferable, and 37×10 -7 / °C or more is particularly preferred. For example, in the manufacture of a TFT-side substrate for a flat panel display, a gate metal film such as copper and a gate insulating film such as silicon nitride may be laminated in this order on an alkali-free glass. If the average thermal expansion coefficient is below the lower limit, the difference in the expansion coefficient between the gate insulating film and the glass becomes too small. Therefore, the effect of the gate insulating film canceling the warping of the glass caused by the formation of the gate metal film becomes small. As a result, the warping of the substrate becomes large, which may cause problems such as problems in transportation and large pattern misalignment during exposure. On the other hand, the average thermal expansion coefficient at 50 to 350°C is 43×10 -7 / ℃ or less is preferable, and 42×10 -7 / ℃ or less is more preferable, and 40×10 -7 / ℃ or less is more preferable, and 39×10 -7 / ° C. or less is particularly preferable. Glass having an average thermal expansion coefficient of not more than the upper limit is resistant to thermal shock and can achieve a high yield.
[0028] The alkali-free glass according to the present embodiment has a viscosity of 10 2 The temperature T2 at which the glass has a poise (dPa·s) is 1500 to 1800°C. T2 is preferably 1550°C or higher, more preferably 1570°C or higher, more preferably 1580°C or higher, and particularly preferably 1600°C or higher. If T2 is below the lower limit, the melting temperature and fining temperature of the glass may deviate, resulting in poor clarity of the glass. If T2 is below the lower limit, the melting furnace may be easily corroded by the molten liquid with a low viscosity, resulting in a short life of the manufacturing equipment. On the other hand, T2 is preferably 1750°C or lower, more preferably 1730°C or lower, even more preferably 1700°C or lower, and particularly preferably 1660°C or lower. If T2 exceeds the upper limit, the glass melts poorly and a high temperature is required, increasing the burden on the manufacturing equipment.
[0029] The alkali-free glass according to the present embodiment has a viscosity of 10 4 The temperature T4 at which the glass becomes poise (dPa·s) is preferably 1400°C or lower, more preferably 1370°C or lower, even more preferably 1350°C or lower, and particularly preferably 1320°C or lower. Glasses having such a T4 are suitable for forming by the float method. If T4 is high, there is a risk of drastically shortening the life of the float bath housing structure and heater.
[0030] The alkali-free glass according to the present embodiment preferably has a glass viscosity of 10 2 The effective thermal conductivity of the glass at temperature T2 where the thermal conductivity is dPa·s is 40 to 65 W / m·K. The effective thermal conductivity at T2 is more preferably 45 W / m·K or more, even more preferably 50 W / m·K or more, and particularly preferably 55 W / m·K or more. Furthermore, the effective thermal conductivity of the glass at T2 is more preferably 63 W / m·K or less, even more preferably 60 W / m·K or less, and particularly preferably 57 W / m·K or less. The effective thermal conductivity is the thermal conductivity measured by the steady-state method (J. Am. Cer. Soc. 44, 1961, pp. 333-339), and is also called the "apparent thermal conductivity." By having the above effective thermal conductivity at temperature T2, an optimal convection velocity occurs during glass melting by heating, making heating efficient, and thus providing a glass product with excellent bubble quality and homogeneity.
[0031] In the alkali-free glass according to this embodiment, the value represented by formula A is preferably 7-30. Formula A: (3.119×10 -4 T2 2 -0.2014T2-17.38)[Fe2O3]+(6.434×10 -7 T2 2 +0.0144T2-7.842)[β-OH] Here, [Fe2O3] is the molar percentage of total iron converted to Fe2O3, and [β-OH] is the value expressed in units of / mm. The above formula A was derived from a detailed analysis of how much the Fe2O3 amount and β-OH value contribute to the decrease in thermal conductivity at different temperatures. The value represented by formula A is an index showing how much the thermal conductivity of the alkali-free glass is reduced compared to when it contains neither moisture nor iron, and the larger the value of formula A, the greater the reduction in thermal conductivity. The value of formula A is more preferably 10 or more, even more preferably 12 or more, and particularly preferably 14 or more. The value of formula A is more preferably 25 or less, even more preferably 20 or less, and particularly preferably 17 or less.
[0032] The alkali-free glass according to the present embodiment preferably has a transmittance of 50% or more at a wavelength of 300 nm, calculated based on a plate thickness of 0.5 mm. This ensures ultraviolet transmittance suitable for use as a substrate or support substrate for various electronic devices. The transmittance is more preferably 60% or more, even more preferably 70% or more, and particularly preferably 80% or more.
[0033] The alkali-free glass according to the present embodiment is preferably in the form of a glass plate. The thickness of the glass plate is preferably 3 mm or less, more preferably 2 mm or less, more preferably 1.5 mm or less, even more preferably 1.2 mm or less, and particularly preferably 0.8 mm or less. The thickness of the glass plate is preferably 0.05 mm or more, more preferably 0.1 mm or more, more preferably 0.15 mm or more, even more preferably 0.2 mm or more, and particularly preferably 0.3 mm or more.
[0034] The alkali-free glass according to the present embodiment can be manufactured by appropriately combining methods known to those skilled in the art. For example, the raw materials of the above components are mixed to obtain the above-mentioned predetermined composition, and the mixture is continuously charged into a melting furnace and heated to 1500 to 1800°C to melt, thereby obtaining molten glass. The obtained molten glass is formed into a glass ribbon of a predetermined thickness by a forming device, and the glass ribbon is gradually cooled and then cut.
[0035] The method for producing the glass and glass plate of the present embodiment is not particularly limited, and various methods can be applied. For example, the raw materials of each component are mixed to obtain a target composition, and then heated and melted in a glass melting furnace. The glass is homogenized by bubbling, stirring, adding a clarifier, etc., and formed into a glass plate of a predetermined thickness by a method such as a float method, a press method, a fusion method, or a down-draw method. After gradual cooling, the glass may be processed as necessary by grinding, polishing, etc., to form a glass substrate of a predetermined size and shape. By using the fusion method, the average cooling rate near the glass transition point is increased, and when the obtained glass plate is further thinned by hydrofluoric acid etching, the surface roughness of the glass plate on the side that has been etched is reduced.
[0036] From the viewpoint of stable production of large-sized sheet glass (for example, one side of 1800 mm or more), it is preferable to use the float method.
[0037] The large substrate is, for example, a glass plate with at least one side of 1800mm or more, and specifically, it is suitable for a glass plate with a long side of 1800mm or more and a short side of 1500mm or more. The alkali-free glass of this embodiment is more preferably a glass plate with at least one side of 2400mm or more, for example, a glass plate with a long side of 2400mm or more and a short side of 2100mm or more, more preferably a glass plate with at least one side of 3000mm or more, for example, a glass plate with a long side of 3000mm or more and a short side of 2800mm or more, particularly preferably a glass plate with at least one side of 3200mm or more, for example, a glass plate with a long side of 3200mm or more and a short side of 2900mm or more, and most preferably a glass plate with at least one side of 3300mm or more, for example, a glass plate with a long side of 3300mm or more and a short side of 2950mm or more.
[0038] Next, a display panel according to an embodiment of the present invention will be described. The display panel of the present embodiment has the alkali-free glass of the above-mentioned embodiment as a glass substrate. As long as it has the alkali-free glass of the above-mentioned embodiment, the display panel is not particularly limited, and may be various display panels such as a liquid crystal display panel and an organic EL display panel.
[0039] Taking the case of a thin film transistor liquid crystal display (TFT-LCD) as an example, it has a display surface electrode substrate (array substrate) on whose surface a gate electrode line and a gate insulating oxide layer are formed, and further a pixel electrode is formed on the surface of the oxide layer, and a color filter substrate on whose surface a RGB color filter and a counter electrode are formed, and a cell is formed by sandwiching a liquid crystal material between the array substrate and the color filter substrate that form a pair. In addition to such a cell, a liquid crystal display panel includes other elements such as peripheral circuits. In the liquid crystal display panel of this embodiment, the alkali-free glass of the above embodiment is used for at least one of the pair of substrates that constitute the cell.
[0040] Next, a semiconductor device according to an embodiment of the present invention has the alkali-free glass of the above-mentioned embodiment as a glass substrate. Specifically, the alkali-free glass of the above-mentioned embodiment is used as a glass substrate for image sensors such as MEMS, CMOS, CIS, etc. Also, the alkali-free glass of the above-mentioned embodiment is used as a cover glass for a display device for projection use, for example, a cover glass for LCOS (Liquid Crystal on Silicon).
[0041] Next, an information recording medium according to an embodiment of the present invention has the alkali-free glass of the above-mentioned embodiment as a glass substrate. Specifically, for example, the alkali-free glass of the above-mentioned embodiment is used as a glass substrate for a magnetic recording medium or an optical disk. Examples of the magnetic recording medium include an energy-assisted magnetic recording medium and a perpendicular magnetic recording medium. EXAMPLES
[0042] Hereinafter, the embodiments of the present invention will be described in more detail with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0043] The raw materials of each component were mixed so that the glass composition was the target composition (unit: mol%) shown in Tables 1 and 2, and melted in a platinum crucible at a temperature of 1650°C for 6 hours while stirring with a stirrer. After melting, the glass was poured onto a carbon plate and held at the glass transition point +30°C for 60 minutes, and then cooled to room temperature at 1°C per minute. The resulting alkali-free glass was mirror-polished to a glass plate, and various evaluations were performed. Examples 1 to 4 and 7 to 10 are examples of the present invention, and Examples 5, 6, 11, and 12 are comparative examples.
[0044] The X-ray intensity of each component on the surface of the glass obtained above was measured using an X-ray fluorescence spectrometer (XRF) (ZSX100e, manufactured by Rigaku Corporation) for quantitative analysis, and the composition was confirmed.
[0045] Average thermal expansion coefficient from 50℃ to 350℃ (unit: × 10 -7The strain point (unit: °C) was measured using a differential thermal dilatometer (TMA) according to the method specified in JIS R3102 (1995). The strain point (unit: °C) was measured by the fiber stretching method according to the method specified in JIS R3103-2 (2001). T2 and T4 were measured using a rotational viscometer. The effective thermal conductivity of glass (hereinafter also referred to as Keff) was measured according to the steady-state method (J. Am. Cer. Soc. 44, 1961, pp. 333-339).
[0046] The effective thermal conductivity (Keff) of the glass at temperature T2 was evaluated after the glass of each example was melted at temperature T2 in a crucible for measuring effective thermal conductivity to obtain a molten glass. The effective thermal conductivity (Keff) was obtained by measuring the thermal conductivity of the crucible containing the molten glass as Kr, the thickness of the bottom of the crucible as dr, the depth of the molten glass in the crucible as dg, the temperature of the surface of the molten glass as Ts, the temperature of the inner bottom surface of the crucible at the interface between the molten glass and the inner bottom surface of the crucible as Tb, and the temperature of the outer bottom surface of the crucible at the outer bottom surface of the crucible as Tr, and using Equation B. Formula B: Keff = Kr{(Tb-Tr) / (Ts-Tb)}(dg / dr) The thermal conductivity Kr of the crucible was determined using Glasses 1 and 2 with known effective thermal conductivities shown in Table 3 by measuring the thickness dr of the bottom surface of the crucible, the depth dg of the molten glass, the temperature Ts of the surface of the molten glass, the interface temperature Tb between the molten glass and the inner bottom surface of the crucible, and the temperature Tr of the outer bottom surface of the crucible, and then using Equation B. The ultraviolet transmittance was measured using a Hitachi U-4100 spectrophotometer in accordance with ISO-9050: 2003. The transmittance was calculated at a wavelength of 300 nm based on a plate thickness of 0.5 mm.
[0047] The β-OH value was measured by mirror polishing both sides of a glass sample to a thickness of 0.70 to 2.0 mm, and then measuring the wavenumber of 4000 to 2000 cm using FT-IR. -1 The transmittance was measured in the range of 4000 cm -1 The transmittance at τ1 [%] and wave number 3600 cm -1The minimum transmittance value near the center of the sample was defined as τ2 [%] and the glass thickness was defined as X [mm], and the β-OH value was calculated using the following formula. The thickness of the glass sample was adjusted so that τ2 was in the range of 20 to 60%. β-OH [mm -1 ]=(1 / X)log 10 (τ1 / τ2)
[0048] [Table 1]
[0049] [Table 2]
[0050] [Table 3]
[0051] As shown in Tables 1 and 2, the glass of Examples 1 to 4 and 7 to 10 has the content of each component, especially Fe2O3 and β-OH value, within the specified range, and ensures a moderately low thermal conductivity while maintaining a high ultraviolet transmittance. Therefore, these can be manufactured as alkali-free glasses with excellent bubble quality and homogeneity. They also have physical properties suitable for use as substrates or support substrates for various electronic devices.
[0052] In contrast, the glasses of Examples 5 and 11 have a high Fe2O3 content, which results in low thermal conductivity, but the necessary UV transmittance cannot be ensured. The glasses of Examples 6 and 12 achieve high UV transmittance by reducing the iron content, but the thermal conductivity is too high. The glasses of Examples 6 and 12 have high thermal conductivity, and the bubble quality and homogeneity of the final product are poor. It can be seen that this defect of the glasses of Examples 6 and 12 is compensated for by the β-OH value in the glasses of Examples 1 to 4 and 7 to 10.
[0053] Although the present invention has been described in detail and with reference to specific embodiments, it will be apparent to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the invention. This application is based on Japanese Patent Application No. 2018-086580 filed on April 27, 2018, the contents of which are incorporated herein by reference. [Industrial Applicability]
[0054] The alkali-free glass according to the embodiment of the present invention can be used for various applications including electronic devices in general, and can be particularly suitably used for applications requiring high ultraviolet transmittance, such as glass substrates or supporting glass substrates for thin display devices and organic EL devices.
Claims
1. The strain point is 665 to 720°C, and the average thermal expansion coefficient at 50 to 350°C is 30 x 10 -7 ~45 x 10 -7 / °C, and the glass viscosity is 10 2 Temperature T at which viscosity becomes dPa·s 2 is 1500°C to 1800°C, In mole percent based on oxide Yes 2 :62~70%, <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> :5~116%、 B 2 O 3 :0.5~12%、 MgO: 5.6-10%, CaO: 4-10%, SrO: 0.1-6%, Fe 2 O 3 : 0.001 to 0.04%, MgO + CaO + SrO + BaO 15.6 to 20.5%, The β-OH value is 0.35 to 0.85 / mm; An alkali-free glass having a value represented by the following formula A of 7 to 30. In addition, in formula A, [Fe 2 O 3 ] is Fe 2 O 3 The value is the mole % of total iron converted into β-OH, and [β-OH] is a value expressed in units of / mm. Formula A: (3.119×10 -4 T 2 2 -0.2014T 2 -17.38)[Fe 2 O 3 ]+(6.434×10 -7 T 2 2 +0.0144T 2 -7.842)[β-OH]
2. Glass viscosity is 10 2 Temperature T at which viscosity becomes dPa·s 2 The alkali-free glass according to claim 1, having an effective thermal conductivity of 40 to 65 W / m·K at 20° C.
3. 2. The alkali-free glass according to claim 1, which has a transmittance of 50% or more at a wavelength of 300 nm based on a plate thickness of 0.5 mm.
4. The alkali-free glass according to claim 1, which is in the form of a glass plate and has a thickness of 0.05 mm to 3 mm.
5. The method for producing an alkali-free glass according to claim 1 , comprising a step of forming the molten glass by a float process or a fusion process.
6. A display panel comprising the alkali-free glass of claim 1.
7. A semiconductor device comprising the alkali-free glass of claim 1.
8. An information recording medium comprising the alkali-free glass according to claim 1.
Citation Information
Patent Citations
Alkali-free glass substrate
JP2005097090A
Non-alkali glass substrate
JP2006036625A
Non-alkali glass substrate
JP2006036626A
Alkali-free glass containing iron and tin as clarifying agents.
JP2010509180A
Alkali-free glass substrate and method for producing same
WO2014175215A1